2018
DOI: 10.2138/am-2018-6282
|View full text |Cite
|
Sign up to set email alerts
|

Pressure, sulfur, and metal-silicate partitioning: The effect of sulfur species on the parameterization of experimental results

Abstract: 11Performing well-controlled metal-silicate partitioning experiments at conditions directly simulating 12 those of a deep magma ocean is difficult. It is therefore common to perform experiments at lower 13 pressures and temperatures, which are used to determine the effects of salient variables. Often, these 14 effects are determined by multiple linear regression of a dataset covering a large range of P-T-15 composition space. In particular, these datasets often contain the results of experiments performed both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…then 𝑙𝑙𝑃𝑃𝑙𝑙𝐷𝐷 𝑅𝑅𝑅𝑅 𝑝𝑝𝑝𝑝/𝑠𝑠𝑠𝑠 obtained at various fO2s depend not only on the FeO content in silicate melt but also on fO2.Li et al (2021) found that the partition coefficients of Re, Mo, As, Sb, and Bi between different sulfide phases (sulfide liquid and monosulfide solid solution) and silicate melt, which elements have variable valence states, at various P-T-fO2 can be empirically described as: 𝑙𝑙𝑃𝑃𝑙𝑙𝐷𝐷 𝑠𝑠𝑠𝑠𝑠𝑠𝑓𝑓𝑠𝑠𝑠𝑠𝑅𝑅/𝑠𝑠𝑠𝑠 = π‘Žπ‘Ž 𝑇𝑇(𝐾𝐾) + 𝑏𝑏 β€’ 𝑃𝑃(πΊπΊπ‘ƒπ‘ƒπ‘Žπ‘Ž)/𝑇𝑇(𝐾𝐾) βˆ’ 𝑛𝑛/2𝑙𝑙𝑃𝑃𝑙𝑙(π‘‹π‘‹π‘Žπ‘Žπ‘…π‘…π‘‚π‘‚) + 𝑐𝑐 β€’ βˆ†π‘Žπ‘Žπ‘€π‘€πΉπΉ + 𝐢𝐢 (11) Li and Audetat (2015), Feng and Li (2019), and Li et al (2021) pointed that if an element M forms not only M-O 2but also M-S 2species in silicate melt, to what extent the 𝑙𝑙𝑃𝑃𝑙𝑙𝐷𝐷 𝑀𝑀 𝑠𝑠𝑠𝑠𝑠𝑠𝑓𝑓𝑠𝑠𝑠𝑠𝑅𝑅/𝑠𝑠𝑠𝑠 is correlated with the FeO content in silicate melt depend significantly on the fraction of the element M that forms M-O 2species. Significant fractions of Pt, Pd, Au, Cu, Ag, and even Mn and W in silicate melt may form sulfidespecies, as discussed in recent studies (e.g.,Zajacz et al, 2013;Bennett and Fei, 2018;Li et al, 2019; Evan et al, 2009;Laurenz et al, 2013).π‘Žπ‘Ž 𝑇𝑇(𝐾𝐾)…”
mentioning
confidence: 99%
“…then 𝑙𝑙𝑃𝑃𝑙𝑙𝐷𝐷 𝑅𝑅𝑅𝑅 𝑝𝑝𝑝𝑝/𝑠𝑠𝑠𝑠 obtained at various fO2s depend not only on the FeO content in silicate melt but also on fO2.Li et al (2021) found that the partition coefficients of Re, Mo, As, Sb, and Bi between different sulfide phases (sulfide liquid and monosulfide solid solution) and silicate melt, which elements have variable valence states, at various P-T-fO2 can be empirically described as: 𝑙𝑙𝑃𝑃𝑙𝑙𝐷𝐷 𝑠𝑠𝑠𝑠𝑠𝑠𝑓𝑓𝑠𝑠𝑠𝑠𝑅𝑅/𝑠𝑠𝑠𝑠 = π‘Žπ‘Ž 𝑇𝑇(𝐾𝐾) + 𝑏𝑏 β€’ 𝑃𝑃(πΊπΊπ‘ƒπ‘ƒπ‘Žπ‘Ž)/𝑇𝑇(𝐾𝐾) βˆ’ 𝑛𝑛/2𝑙𝑙𝑃𝑃𝑙𝑙(π‘‹π‘‹π‘Žπ‘Žπ‘…π‘…π‘‚π‘‚) + 𝑐𝑐 β€’ βˆ†π‘Žπ‘Žπ‘€π‘€πΉπΉ + 𝐢𝐢 (11) Li and Audetat (2015), Feng and Li (2019), and Li et al (2021) pointed that if an element M forms not only M-O 2but also M-S 2species in silicate melt, to what extent the 𝑙𝑙𝑃𝑃𝑙𝑙𝐷𝐷 𝑀𝑀 𝑠𝑠𝑠𝑠𝑠𝑠𝑓𝑓𝑠𝑠𝑠𝑠𝑅𝑅/𝑠𝑠𝑠𝑠 is correlated with the FeO content in silicate melt depend significantly on the fraction of the element M that forms M-O 2species. Significant fractions of Pt, Pd, Au, Cu, Ag, and even Mn and W in silicate melt may form sulfidespecies, as discussed in recent studies (e.g.,Zajacz et al, 2013;Bennett and Fei, 2018;Li et al, 2019; Evan et al, 2009;Laurenz et al, 2013).π‘Žπ‘Ž 𝑇𝑇(𝐾𝐾)…”
mentioning
confidence: 99%